Dietary satisfaction and quality of life in chronic kidney disease patients on low-protein diets: a multicentre study with long-term outcome data (TOrino-Pisa study). Issue 5 (21st August 2019) - Piccoli, Giorgina Barbara; Di Iorio, Biagio Raffaele; Chatrenet, Antoine; D'Alessandro, Claudia; Nazha, Marta; Capizzi, Irene; Vigotti, Federica Neve; Fois, Antioco; Maxia, Stefania; Saulnier, Patrick; Cabiddu, Gianfranca; Cupisti, Adamasco
Abstract: Background: Concerns about adherence and quality of life (QoL) limit the diffusion of low-protein diets (LPDs) as a way to slow chronic kidney disease (CKD) progression and postpone dialysis. The aim of this multicentre study is to assess dietary satisfaction in stable CKD patients. Methods: This was a multicentre cross-sectional study with long-term follow-up data. Prevalent patients on LPD for at least 6 months were selected in four Italian centres. QoL was assessed using the World Health Organization Quality of Life questionnaire, and diet satisfaction with the Modification of Diet in Renal Disease satisfaction questionnaire. Comorbidity was assessed by Charlson Comorbidity Index, estimated glomerular filtration rate (eGFR) was calculated by the CKD Epidemiology Collaboration equation and protein intake by Maroni–Mitch formula. Survival was analysed with Kaplan–Meier curves and Cox Proportional Hazard Model. Results: Four hundred and twenty-two CKD Stages 3–5 patients were enrolled. Over 95% were on moderately restricted diets (0.6 g/kg/day). Compliance was good (protein intake: 0.59 g/kg/day at baseline, 0.72 at the end of follow-up). Median dietary satisfaction was 4 on a 1–5 scale. QoL was not affected by the type of diet, but was influenced by age, comorbidity and setting of care. Two years later, at the end of follow-up, 66.6% of the patients were still on a diet; the main causes of discontinuation were dialysis and death. The dropout rate was low (5.5%); in Cox analysis, patient and renal survival were influenced by age and eGFR, but not by QoL, setting of care or type of diet. Conclusions: LPDs are compatible with high dietary satisfaction and minimal dropout, at least in patients who are able to follow such a diet for at least 6 months.